2018
DOI: 10.1007/s12282-018-0872-6
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness analysis of lipegfilgrastim as primary prophylaxis in women with breast cancer in Australia: a modelled economic evaluation

Abstract: Lipegfilgrastim was likely to be a cost-effective alternative to pegfilgrastim as primary prophylaxis. The sensitivity analysis showed the confidence interval for the cost and benefit outcomes overlapped to a great extent, suggesting an insignificant difference.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 38 publications
2
4
0
Order By: Relevance
“…Our analysis demonstrated that PEG-rhG-CSF was more costeffective compared to rhG-CSF as primary prophylaxis under the WTP threshold of one-time GDP per capita. The result was similar to Xia et al ( 2020), but different from Akpo et al (2017), Gao and Li (2018), and Li-Tian et al ( 2019), whose results showed that PEG-rhG-CSF strategy was cost-saving than rhG-CSF. Compared to randomized trials, our study showed that the incidence of FN for the short-acting group was higher than these studies, and the cost of the long-acting group was in excess of approximately ¥2,500, but the price gap in Akpo et al (2017) and Gao and Li (2018) was zero.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Our analysis demonstrated that PEG-rhG-CSF was more costeffective compared to rhG-CSF as primary prophylaxis under the WTP threshold of one-time GDP per capita. The result was similar to Xia et al ( 2020), but different from Akpo et al (2017), Gao and Li (2018), and Li-Tian et al ( 2019), whose results showed that PEG-rhG-CSF strategy was cost-saving than rhG-CSF. Compared to randomized trials, our study showed that the incidence of FN for the short-acting group was higher than these studies, and the cost of the long-acting group was in excess of approximately ¥2,500, but the price gap in Akpo et al (2017) and Gao and Li (2018) was zero.…”
Section: Discussionsupporting
confidence: 84%
“…The result was similar to Xia et al ( 2020), but different from Akpo et al (2017), Gao and Li (2018), and Li-Tian et al ( 2019), whose results showed that PEG-rhG-CSF strategy was cost-saving than rhG-CSF. Compared to randomized trials, our study showed that the incidence of FN for the short-acting group was higher than these studies, and the cost of the long-acting group was in excess of approximately ¥2,500, but the price gap in Akpo et al (2017) and Gao and Li (2018) was zero. This may be one of the reasons why their results differed from ours.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…As a result of its novel pegylation method [13,14], lipegfilgrastim has a different pharmacokinetic and pharmacodynamic profile than pegfilgrastim, specifically higher cumulative exposure and slower clearance, and induces a longer-lasting increase in ANC at equivalent doses [15]. Analyses utilizing data from patients with breast cancer suggest that lipegfilgrastim is likely to be a cost-effective alternative to pegfilgrastim for primary prohylaxis of complications of chemotherapy-induced neutropenia and associated complications [28,29].…”
Section: Discussionmentioning
confidence: 99%